Ethnic tolerance in Sabah: an analysis of the factors affecting the harmony of the people in Sabah - Budi Anto Mohd Tamring; Bernadette Tobi; Mohd Sohaimi Esa (Solid State Technology, 2020)
This paper explains the factors influencing the level of tolerance that exist among the various ethnics and religions in Sabah. It also analyses, at the macro level, the social cohesion of the societies in Sabah from the aspect of structural social relations as they relate to several micro-level studies made by researchers in Sabah, particularly in relation to issues of ethnic tolerance in the state. It therefore, appeared that the various ethnic and religious communities in Sabah are at a good ethnic tolerance level compared to other states in Peninsular Malaysia; this must be understood within a different context. This understanding must take into account the history of the various ethnic communities in Sabah as well as explain the cultural openness that causes the relaxation of cultural identity that is present among the population. Hence, it must be understood that the high ethnic tolerance level in Sabah is not something new, but have existed long before the arrival of the colonialists where the situation has manifested itself through the various forms of social relations, including the most intimate family relations (marriage).